Vertibral artery Dissection secondary to Malignant hypertension precipitating a posterior circulation stroke - Avi Singh Gandh Gandh; Shruti Vadali; Jivtesh Singh; Sanwal Singh Mehta (International Journal of Medical Students)
Background: Diagnosing posterior circulation strokes is challenging due to non-focal symptoms and their overlap with anterior circulation ischemia. Common presentations include lateral medullary syndrome (Wallenberg) and cerebellar infarctions, with symptoms like nystagmus, truncal ataxia, tongue deviation, internuclear ophthalmoplegia, and contralateral pain and temperature impairment. These strokes are often missed on NCCT head scans. High clinical suspicion and evolving neurological signs should prompt a CT angiogram of the head and neck, though MR angiography remains the gold standard for confirming vertebral artery dissection.